Analisis Perilaku Konsumen Terhadap Minat Beli di Pasar Seni To’pao - Nopi Sapa’; Dina Ramba; Rati Pondissing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Nopi 'Sapa' 2023. Analysis of Consumer Behavior on Purchase Intention at the To'Pao Art Market. This research is to find out how to analyze consumer behavior towards buying interest in the to'pao art market. This type of research uses descriptive qualitative research in which researchers develop consumer behavior towards buying interest at to'pao art markets. The results of this study indicate that there are several factors that influence buying interest in the to'pao art market, namely: 1. Cultural factors influence a person's purchasing decision to follow the customs of the community, or ethnic groups collect and wear when attending certain events. 2. Social factors influence the influence of reference groups, family, and roles and status to cause a person to make a purchase intention in order to gain recognition in society. 3. Personal factors are influential because work, age, and economic conditions encourage someone to make a purchase intention. 4. Psychological factors affect purchase intention through motivation, information, and influence from other people so that it automatically causes a positive perspective on an item.